Contaminated air conditioners as potential source for contaminating operation theater environment - Kelkar, Uday Siddharaj; Kulkarni, Sandhya Sadanand (International Journal of Infection Control, 2011)
Five patients developed endophthalmitis after cataract surgery. On evaluation of operation-theater complex, fungal spores were demonstrable from environment and surfaces. Air conditioner’s filters were grossly contaminated. Aspergillus and Mucor Spp. were isolated. Phonotypically similar fungi (Aspergillus Spp. from two and Mucor Spp. from one) were isolated from three of the patients. As a follow up study filters of the air conditioning devices in twenty five operating rooms of hospitals nearby were evaluated periodically. The results of this surveillance study were used to educate the hospitals about need for routine cleaning and disinfection of gadgets like air conditioners minimizing the chances of proliferation and dispersal of potentially pathogenic fungi. Key Words: Operation Theater, Air conditioners, Fungi, Surveillance